2021
DOI: 10.1186/s13063-021-05301-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimising AVATAR therapy for people who hear distressing voices: study protocol for the AVATAR2 multi-centre randomised controlled trial

Abstract: Background AVATAR therapy is a novel intervention targeting distressing auditory verbal hallucinations (henceforth ‘voices’). A digital simulation (avatar) of the voice is created and used in a three-way dialogue between participant, avatar and therapist. To date, therapy has been delivered over 6 sessions, comprising an initial phase, focusing on standing up to a hostile avatar, and a second phase in which the avatar concedes and focus shifts to individualised treatment targets, including beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…In the field of e-health mental interventions, an avatar is a digital self-representation of the person, in line with the identity and character attributed. Through the avatar, the therapist can interact with the patient and the patient can act within the virtual space, simulating behaviors and attitudes that they would display in vivo [ 34 ]. The use of avatars in e-mental health interventions represents a nascent area of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of e-health mental interventions, an avatar is a digital self-representation of the person, in line with the identity and character attributed. Through the avatar, the therapist can interact with the patient and the patient can act within the virtual space, simulating behaviors and attitudes that they would display in vivo [ 34 ]. The use of avatars in e-mental health interventions represents a nascent area of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…All the research team members who contributed to the final iteration of the coding frame have a clinical psychology or psychiatry background and, with the exception of NE, they all have been trained and have delivered AVATAR therapy and have participated in data analyses of various studies of trial data (MRC, TW, CE, PAG and TC). Two independent completers of AVATAR therapy (current members of the PPI group for the new multi-centre randomised controlled trial of AVATAR therapy ISRCTN55682735, [ 10 ]) reviewed and contributed to the refinement of wording of themes and subthemes separately.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary encouraging evidence for the efficacy of the therapy has been reported in two independent pilot studies [ 6 , 7 ] and further supported by the findings of a large fully-powered randomised controlled trial comparing AVATAR therapy and Supportive Counselling [ 8 ], which showed a post-therapy effect size of d = 0.8 on the primary outcome (total score on the Psychotic Symptom Rating Scales, auditory hallucinations subscale (PSYRATS–AH, [ 9 ]). AVATAR therapy is now being further examined for optimal delivery, effectiveness and cost-effectiveness in a new multi-centre randomised controlled trial ISRCTN55682735 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Providing psychological therapies for paranoia and distressing hallucinations alongside pharmacotherapy and other medical treatments is now well-established in clinical guidelines ( 1 ) and there continues to be considerable innovation in the types of therapies being developed for positive symptoms [e.g. ( 2 , 3 )]. However, the negative symptoms of schizophrenia such as avolition-apathy and diminished expressive abilities have remained a major source of distress and arrested recovery that frequently present a significant treatment challenge ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%